Niger : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses the external stability of Niger. Niger's real effective exchange rate has been depreciating recently, echoing fluctuations of the euro against the US dollar. A model-based analysis of Niger's external sector suggests that the real effective exchange rate is broadly in line with macroeconomic fundamentals, which is also consistent with the findings of the 2014 external sector assessment. However, broader competitiveness indicators are worrisome, despite some improvement noted in recent years. The recent depreciation of the naira also suggests some weakening in competitiveness, at least with Nigeria.